The Micro-situational Context of Sexual Offences Against Adult Women: Unpacking the Role of Guardianship Intensity in Disruption. (June 2021) - Cook, Alana; Leclerc, Benoit; Reynald, Danielle M.; Wortley, Richard
The current study explores the way guardianship is perceived by offenders and the extent to which it affects the likelihood of disruption in sexual offences against adult females. Specifically, we compare the micro-situational contexts in which sexual offences against adult females are disrupted to those in which these offences are completed. Data on sexual crime events was collected from 138 adult males who were incarcerated for committing a sexual offence against a woman using a self-report questionnaire incorporating a crime-script framework. We found that the presence or availability of a guardian does not guarantee offence disruption. Rather, action taken by the guardian is the critical factor which determines a sexual offender's decision to cease the offence.